2020 IEEE International Workshop on Metrology for Agriculture and Forestry (MetroAgriFor) 2020
DOI: 10.1109/metroagrifor50201.2020.9277657
|View full text |Cite
|
Sign up to set email alerts
|

Neural networks for Pest Detection in Precision Agriculture

Abstract: Apple is one of the most produced fruit crops in the world. Recent advances in Artificial Intelligence and the Internet of Things can reduce production costs and improve crop quality by providing prompt detection of dangerous parasites. This paper presents an effective solution to automate the detection of the Codling Moths. The system takes pictures of trapped insects in the orchard, analyzes them through a DNN algorithm, and sends alarms to the farmer in case of a positive detection. The system is fully auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 27 publications
(21 reference statements)
0
10
0
Order By: Relevance
“…In 2020, Segalla et al [24] also wrote about an automated trap which is very similar to the trap proposed by Brunelli et al [23]. The two articles show high similarity.…”
Section: Earlier Prototype Trapsmentioning
confidence: 87%
See 1 more Smart Citation
“…In 2020, Segalla et al [24] also wrote about an automated trap which is very similar to the trap proposed by Brunelli et al [23]. The two articles show high similarity.…”
Section: Earlier Prototype Trapsmentioning
confidence: 87%
“…However, there are differences as well. Since the Intel Movidius Neural Compute Stick is rather power demanding, the authors of [24] measured the energy consumption of the Raspberry Pi 3 and 4 devices with and without the accelerator stick. They found that the Raspberry Pi 3 with the accelerator stick requires the least amount of energy to run the moth counter software.…”
Section: Earlier Prototype Trapsmentioning
confidence: 99%
“…Brunelli et al [29] presented an ultra-low power smart camera capable of detecting and recognizing pests in an apple field using a neural networks approach. An evolution of this system used Raspberry Pi [30] and Intel Movidius Neural Compute Stick [31], both powered by a solar panel. Table 1 compares these works and IndoorPlant according to the type of sensor they use, which plant species were cultivated, data analysis and storage, prediction technique, and use of historical contexts.…”
Section: Related Workmentioning
confidence: 99%
“…With this, IndoorPlant tells the farmer to modify the cultivation parameter; however, the farmer needs to approve this change. Another aspect is that the previous studies had only one specific service, such as predicting the temperature and humidity of the greenhouse [19], intelligent irrigation [23] or monitoring environment data [26][27][28][29][30][31]. IndoorPlant, on the other hand, can provide several intelligent services for the user, such as predicting harvest time, recommending improvements in cultivation, and alarms for any problem found in cultivation.…”
Section: Related Workmentioning
confidence: 99%
“…Deep learning techniques are recently used to overcome these limitations and achieve a completely automated, realtime pest monitoring system by removing the human from the loop [20]. [21] is one of the recent works that exploit ML techniques to classify insects.…”
Section: Related Workmentioning
confidence: 99%